Fibrin Clot Architecture in Acute Ischemic Stroke Treated With Mechanical Thrombectomy With Stent-Retrievers - Cohort Study - Krajíčková, Dagmar; Krajina, Antonín; Šteiner, Ivo; Vyšata, Oldřich; Herzig, Roman; Lojík, Miroslav; Chovanec, Vendelín; Raupach, Jan; Renc, Ondřej; Waishaupt, Jan; Vítková, Eva; Dulíček, Petr; et al. (Circulation journal, 2018)
BACKGROUND: The composition of intra-arterial clots might influence the efficacy of mechanical thrombectomy (MT) in ischemic stroke (IS) due to the acute occlusions within large cerebral arteries. The aims were to assess the factors associated with blood clot structure and the impact of thromboembolus structure on MT using stent-retrievers in patients with acute large artery IS in the anterior circulation. METHODS AND RESULTS: In an observational cohort study, we studied the components of intra-arterial clots retrieved from large cerebral arteries in 80 patients with acute IS treated with MT with or without i.v. thrombolysis (IVT). Histology of the clots was carried out without knowledge of the clinical findings, including the treatment methods. The components of the clots, their age, origin and semi-quantitative graded changes in the architecture of the fibrin components (e.g., "thinning") were compared via neuro-interventional, clinical and laboratory data. The most prominent changes in the architecture of the fibrin components in the thromboemboli were associated with IVT (applied in 44 patients; OR, 3.50; 95% CI: 1.21-10.10, P=0.02) and platelet count (OR, 2.94; 95% CI: 1.06-8.12, P=0.04). CONCLUSIONS: In patients with large artery IS treated with the MT using stent-retrievers, bridging therapy with IVT preceding MT and higher platelet count were associated with significant changes of the histological structure of blood clots.
Keywords: Endovascular procedure; senioři; Cohort Studies; trombóza; Female; Male; mladý dospělý; Fibrin; Aged; Middle Aged; Treatment outcome; Brain Ischemia; Young Adult; Stroke; mechanická trombolýza; Thrombectomy; stenty; ischemie mozku; Stents; kohortové studie; Thrombosis; Blood clot; mužské pohlaví; Platelet Count; ženské pohlaví; Adult; fibrin; senioři nad 80 let; cévní mozková příhoda; dospělí; lidé středního věku; počet trombocytů; Aged, 80 and over; lidé; Humans; Mechanical Thrombolysis